Animal experimentation : working towards a paradigm change - Herrmann, Kathrin; Herrmann, Kathrin (Human-Animal Studies, 2019)
Animal experimentation has been one of the most controversial areas of animal use, mainly due to the intentional harms inflicted upon animals for the sake of hoped-for benefits in humans. Despite this rationale for continued animal experimentation, shortcomings of this practice have become increasingly more apparent and well-documented. However, these limitations are not yet widely known or appreciated, and there is a danger that they may simply be ignored. The 51 experts who have contributed to Animal Experimentation: Working Towards a Paradigm Change critically review current animal use in science, present new and innovative non-animal approaches to address urgent scientific questions, and offer a roadmap towards an animal-free world of science.
Keywords: Animal experimentation; Ethics & moral philosophy